Population structure of palms in rainforests frequently impacted by cyclones - DIAN LATIFAH; ROBERT A. CONGDON; JOSEPH A. HOLTUM (Society for Indonesian Biodiversity, 2017)
Abstract. Latifah D, Congdon RA, Holtum JA. 2017. Population structure of palms in cyclone-dependent rainforests. Biodiversitas 18: 41-50.Tropical cyclones may act as important ecological drivers in northern Australia including north Queensland, as several cyclones impact this region each year between November and May. Extensive research has been conducted to investigate how the population structure of rainforest species respond to cyclonic disturbances. However, there have been few such studies on palms although they are important components of rainforests. Therefore, these study aimed to investigate how the population structure of Arenga australasica (H. Wendl. & Drude) S. T. Blake ex H. E. Moore, Calamus australis Mart., C. moti F. M. Bailey, Hydriastele wendlandiana (F. Muell.) H. Wendl. & Drude and Licuala ramsayi var. ramsayi (F. Muell.) H. Wendl. & Drude responded to a cyclone, as shown by size class reflecting mass recruitment after a periodic major disturbance (case study: Cyclone Larry). The field research was carried out in three study sites: Tam OShanter/Djiru National Park, Clump Mountain National Park and Kurrimine Beach Conservation Park located near Mission Beach and Kurrimine Beach, in north Queensland. Observations were made of life stage distribution, height and dbh distribution and wind resistance. We found that responses of the population structures of these rainforest palms varied following cyclonic disturbance by demonstrating higher densities of seedlings and juveniles, suggesting populations would be retained. More seedlings of C. australis and C. moti were found in gaps with higher canopy openness; oppositely, less seedlings of L. ramsayi were encountered under sites with lower sunlight. Keywords: disturbance, palms, population structure, northern Australia